Pulmonary embolism: an EFIM guideline critical appraisal and adaptation for practicing clinicians - Becattini, Cecilia; Kokorin, Valentin A.; Lesniak, Wiktoria; Marin-Leon, Ignacio; Medrano, Francisco J.; Morbidoni, Laura; Marra, Alberto M.; Biskup, Ewelina; Riera-Mestre, Antoni; Dicker, Dror (European journal of internal medicine, 2022)
Background - Several trials have been conducted in the last decades that challenged the management of patients with acute pulmonary embolism (PE) in terms of diagnosis and treatment. Updated international clinical practice guidelines (CPGs) endorsed the evidence from these trials. The aim of this document was to adapt recommendations from existing CPGs to assist physicians in decision making concerning specific and complex scenarios related to acute PE. - Methods - The flow for the adaptation procedure was first the identification of unsolved clinical issues in patients with acute PE (PICOs), then critically appraise the existing CPGs and choose the recommendations, which are the most applicable to these specific and complex scenarios. - Results - Five PICOs were identified and CPGs appraisal was performed. Concerning diagnosis of PE when computed tomographic pulmonary angiography is not available/contraindicated and d-dimer is less specific, perfusion lung scan is the preferred option in the majority of clinical scenarios. For the treatment of PE when relevant clinical conditions like pregnancy or severe renal failure are present heparin is to be used. Poor evidence and low-level recommendations exist on the best bleeding prediction rule in patients treated for PE. The duration of anticoagulation needs to be tailored concerning the presence of predisposing factors for index PE and the consequent risk for recurrence. Finally, recommendations on the opportunity to screen for cancer and thrombophilia patients without recognized thrombosis risk factors for PE are reported. Overall, 35 recommendations were endorsed and the rationale for the selection is reported in the main text. - Conclusion - By the use of proper methodology for the adaptation process, this document offers a simple and updated guide for practicing clinicians dealing with complex patients.
Online verfügbar 11 December 2021, Version des Artikels 28 January 2022
Gesehen am 28.09.2022